PARTISIPASI PETANI SAYUR JAWA BARAT TERHADAP AKSES LAHAN - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Agros Journal of Agriculture Science, 2024)
Vegetable farmers in West Java currently are generally small farmers whose land holdings are less than half a hectare. Of the approximately 14 million smallholder farmers throughout Indonesia, the majority are on the island of Java, of which around 2 million smallholder farmers live in West Java. This indicates that it is increasingly difficult for West Java farmers to have the ability to expand their land, so they need help from the government to increase access to land. Based on this explanation, the aim of this research is to describe the participation of vegetable farmers in increasing land access control in West Java. The population in this study were West Java potato farmers in 2023 with 500 farmers taking respondents. Survey Methods and PRA (Participatory Rural Appraisal). This is the method used in this research. This research shows that farmers pay an average land rental of 1.1 million rupiah per hectare, coupled with an increase in land rental prices by an average of 5% per year. The result of this is that there are only 63 farmers who are able to rent two to three plots of land and there is only one farmer who rents four plots of land. Apart from that, farmers who sell land have the lowest farming experience compared to others. Keywords: Vegetable Farmers, Land Area, Small Farmers, West Java INTISARIPetani sayuran di Jawa Barat saat ini pada  umumnya merupakan petani gurem yang penguasaan lahannya kurang dari setengah hektar. Dari sekitar 14 juta orang petani gurem yang ada di seluruh Indonesia, didominasi di pulau Jawa yang diantaranya yaitu sekitar 2 juta orang petani gurem tinggal di Jawa Barat. Hal ini mengindikasikan bahwa petani Jawa Barat semakin sulit untuk mempunyai kemampuan dalam memperluas lahannya sehingga perlu dibantu oleh pemerintah untuk dapat meningkatkan akses terhadap lahan. Berdasarkan paparan tersebut tujuan penelitian ini adalah untuk mendeskripisikan partisipasi petani sayuran terhadap peningkatan penguasaan akses lahan di Jawa Barat. Populasi pada penelitian ini adalah petani kentang Jawa Barat tahun 2023 dengan responden yang diambil adalah 500 petani. Metode Survey dan PRA (Partisipatory Rural Appraisal). Menjadi metode yang digunakan pada penelitian ini. Penelitian ini menujukan Petani membayar sewa lahan rata-rata sebesar 1,1 juta rupiah per hektarnya, ditambah dengan adanya peningkatan harga sewa lahan rata-rata sebesar 5% per tahun. Akibat dari hal tersebut adalah hanya ada 63 petani yang mampu menyewa lahan sebanyak dua sampai tiga plot dan hanya ada satu orang petani yang menyewa lahan sebanyak empat plot. Selain itu, petani yang melakukan penjualan lahan pengalaman usahataninya paling rendah dibanding yang lainnya. Kata Kunci : Petani Sayuran, Luas Lahan, Petani Gurem Jawa Barat.